Maternal embryonic leucine zipper kinase inhibits epithelial-mesenchymal transition by regulating transforming growth factor-β signaling - Cheng, Jianjian (Oncol Lett, 2017)
Maternal embryonic leucine zipper kinase (MELK) performs an important role in self-renewal and proliferation of progenitor cells or tumor stem cells, and is expressed in aggressive cancers, contributing to tumorigenesis. However, the function of MELK in metastasis is unknown. In the present study, the lung cancer A549 cell line was utilized in order to study the role of MELK in epithelial-mesenchymal transitions (EMTs), the initial step of tumor metastasis. It was identified that transforming growth factor-β (TGF-β) could downregulate the expression of MELK, and that MELK could inhibit EMT by regulating TGF-β signaling. MELK can interact with Smad proteins, which represses TGF-β/Smad-mediated signaling activity. The findings of the present study identified the effect of MELK in TGF-β signaling and the EMT process.